Switching from febuxostat to dotinurad, a novel selective urate reabsorption inhibitor, may substantially reduce serum urate levels, through URAT1 inhibition, potentially without adversely affecting ABCG2 function: findings from the SWITCH SURI study - Osonoi, Takeshi; Shirabe, Shinichiro; Saito, Miyoko; Hosoya, Mitsuru; Watahiki, Norie; Douguchi, Satako; Ofuchi, Kensuke; Katoh, Makoto (Frontiers in Endocrinology, 2025)
BackgroundDotinurad is a novel selective urate transporter 1 (URAT1) inhibitor recently introduced in Japan. This study aims to evaluate the efficacy and safety of dotinurad in hyperuricemic patients with type 2 diabetic kidney disease by comparing serum levels of urate and plasma and urinary levels of indoxyl sulfate excreted via the urate excretion transporter ATP binding cassette subfamily G member 2 (ABCG2), as indices, with baseline levels after switching from febuxostat to dotinurad in hyperuricemic patients with type 2 diabetic kidney disease (DKD).MethodsIn this single-center, single-arm, open-label, prospective study, 37 hyperuricemic patients with DKD who had serum urate levels >6.0 mg/dL despite at least 3 months of febuxostat 20 mg/day were enrolled. Dotinurad was administered once daily for 24 weeks (starting at 0.5 mg/day, titrated up to 4 mg/day). The primary outcome was the proportion of patients achieving serum urate ≤6.0 mg/dL at week 24. Secondary outcomes included changes in serum urate, plasma and urinary indoxyl sulfate levels, and safety parameters.ResultsAt week 24, 70.3% of patients (26/37) achieved serum urate ≤6.0 mg/dL, significantly exceeding the predefined threshold of 30% (p < 0.01). Serum uric acid levels transiently increased from baseline 4 weeks after switching (p<0.01), but decreased to a mean of 5.5 mg/dL by 24 weeks (p<0.01). Urinary uric acid excretion increased significantly during the observation period, reflecting improved uric acid clearance. Urinary indoxyl sulfate (corrected for creatinine) showed significant increases at weeks 4 and 12, and indoxyl sulfate clearance was significantly improved at week 24. No clinically meaningful changes were observed in renal function, glycemic control, lipid profile, or blood pressure. Adverse events occurred in 17 patients (45.9%), mostly mild; two (5.4%) experienced serious events, with no drug-related safety concerns identified.ConclusionSwitching to dotinurad was significantly reduced serum urate levels via URAT1 inhibition, potentially without adversely affecting ABCG2 function, with the majority of patients achieving the target urate level (≤6.0 mg/dL) by week 24. Including the absence of new safety concerns, dotinurad appears to be an effective urate-lowering therapy for patients with type 2 DKD.